The Effect of Stress Ball on Anxiety and Pain Levels in Angiography: A Randomized Controlled Trial - Yuksel, Dilan; Gunes, Dilek (Wiley, 2024)
Background: Coronary angiography, an invasive diagnostic procedure, often induces pain and anxiety in patients. Despite the potential for alleviating discomfort, the use of stress balls as a nonpharmacological intervention during angiography remains underexplored. Objective: This study is aimed at investigating the impact of stress ball application on pain and anxiety levels in patients undergoing angiography. Methods: This randomized controlled trial was conducted on adult patients undergoing angiography at a Cardiovascular Surgery Clinic in Eastern Turkey between January 2023 and June 2023. A total of 120 patients were randomly assigned to receive stress ball application in addition to routine care. Data collection utilized the Numerical Rating Scale (NRS), Patient Information Form, and State-Trait Anxiety Inventory (STAI). Results: Analysis revealed a significantly lower increase in mean NRS posttest scores among patients in the experimental group compared to the control group (p<0.05). Additionally, the mean STAI posttest score demonstrated a significant decrease (p<0.05) in the experimental group. A positive and significant correlation was observed between the mean NRS and STAI posttest scores among study group patients (p<0.05), indicating a reduction in anxiety levels with decreasing pain. Conclusion: The application of stress balls during angiography was associated with decreased anxiety and pain levels in patients. Stress ball intervention may serve as a beneficial adjunct to pharmacological treatments. This study underscores the potential of nonpharmacological interventions in enhancing patient comfort during invasive procedures.
Keywords: angiography; anxiety; nursing; pain; stress ball